EXCHANGING SPORT MANAGEMENT SKILLS FROM POPULAR SPORT IN THE GLOCALIZATION PERSPECTIVE FOR YOUNG PEOPLE: THE OPPORTUNITY TO INCREASE THE CRICKET IN BRAZIL AND FOOTBALL IN INDIA (Fiep Bulletin - online, 2020)
Globalisation is the process that is linking people, neighbourhoods, cities, regions and countries. The process of conducting business according to both local and global considerations is known as glocalisation. According to KPMG (2016), the global sports market is estimated at USD 600–700 billion; accounting for approximately 1 percent of the global Gross Domestic Product (GDP). It exercises a significant impact on the global economy due to its close association with education, real estate, tourism and other sectors. The objective of the study was to analyse critically some opportunities of social development for the future youth generations through the medium of sports in two developing countries from the BRICS.